Freshwater zooplankton diversity and culture of selected species with emphasis on reproductive capacities and nutritional contents - Ahmad Dini, Umi Wahidah (2023)
Zooplankton forms a critical link between the base of the aquatic food web and the top-level consumers; therefore, they are important live-feed organisms in the aquaculture industry. However, the unavailability and unstable production of highly nutritious live feeds are major bottlenecks for the aquaculture industry. Thus, understanding water quality and food requirements for zooplankton is pivotal to the success of sustainable production of zooplankton as live feed in hatcheries. Therefore, the current study aimed to evaluate the distribution and diversity of freshwater zooplankton and identify prospective candidates as live feeds. Subsequently, this study was conducted to ascertain the ideal conditions for zooplankton culture and to assess the effectiveness of microalgae-bacteria encapsulation in enhancing zooplankton quality. A study on zooplankton distribution was carried out at 20 different freshwater water bodies in Malaysia. Physicochemical parameters were measured in situ, while water and zooplankton samples were collected for nutrient analyses and for zooplankton identification and enumeration. Selected zooplankton species were molecularly characterised using the 18S rDNA approach. Each of the selected zooplankton species was exposed to several parameters, including temperature (25 °C, 27 °C and 30 °C), pH (pH 5, pH 7, and pH 9), unionized-ammonia, NH3-N (0.1 mg L-1, 0.3 mg L-1, and 0.5 mg L-1), and diets (13 diets, including mono and mixed diets). Each treatment was conducted in triplicate. Daily observations were performed for the life cycle, population density, and population growth rate. Proximate analysis was conducted according to standard methods, and fatty acids were analysed using a gas chromatograph–mass spectrometer (GC-MS). A total of 58 zooplankton species, consisting of 12 species of cladocerans, 10 species of copepods, and 36 species of rotifers, were recorded. Environmental parameters associated with eutrophication (high nutrients, chlorophyll a, turbidity, and low water transparency with a Global Test, ρ = 0.508) affect the diversity and composition of zooplankton. Several tolerant species such as Ceriodaphnia cornuta, Brachionus calyciflorus, Keratella cochlearis, Trichocerca similis, Thermocyclops crassus, and Mesocyclops thermocyclopoides can thrive in high eutrophic conditions, indicating that these species could serve as indicators. Among the three freshwater zooplankton groups, Cladocera was selected due to its reproduction mode and nutritional quality. Three species (C. cornuta, Moina micrura and Diaphanosoma excisum) of cladocerans were selected for cultivation based on their abundance and differences in size.The present results pointed out that the optimum water quality requirements for all three cladocerans were 27 ℃, pH 7, and 0.1 mg L-1 NH3-N, which supported the fastest maturation, the highest reproductive capacities (production of eggs, offspring, and clutches), and maximized the nutritional contents of all cladocerans species. Furthermore, regarding diets, the combination of the bacterium, Ochrobactrum haematophilum with high-quality microalgae, especially the T10 diet (Cyclotella meneghiniana + O. haematophilum) found to be the ideal diet for all cladocerans, which enhanced the reproductive capacities and nutritional composition. Meanwhile, cyanobacteria diets (Microcystis aeruginosa and Planktothrix agardhii) were considered as poor diets which hindered the growth of cladocerans. However, the addition of O. haematophilum to M. aeruginosa and P. agardhii diets (T12 and T13) increased the population density and reproductive capacities of all cladocerans but not the nutritional contents. Overall, the selection of optimal culture conditions and microalgaebacteria consortium have important implications for improving the production of high-quality cladocerans for sustainable cultivation, which can be utilized as high-quality live feeds in the aquaculture industry.